Pengaruh Kompensasi dan Kepemimpinan Transaksional terhadap Turnover Intention melalui Kepuasan Kerja di Leo Fashion Group - Hadziq Jauhary; Suhana Suhana (SAFE-Network, 2026)
The increasingly intense competition in the Indonesian fashion retail industry requires companies not only to focus on marketing strategies and product quality but also to manage human resources effectively. One of the critical problems faced by retail companies is the high level of employee turnover intention, which negatively affects operational stability, service quality, and overall organizational performance. This study aims to examine the effect of compensation and transactional leadership on turnover intention, with job satisfaction serving as a mediating variable. This research employed a quantitative explanatory approach using a survey method. The population consisted of 60 employees of Leo Fashion Group, and a saturated sampling technique was applied, in which all members of the population were included as respondents. Data were collected through structured questionnaires distributed via Google Form using a five-point Likert scale and were analyzed using multiple linear regression analysis and mediation testing with the assistance of SPSS. The results indicate that compensation has a negative but insignificant effect on turnover intention. Meanwhile, transactional leadership has a negative and significant effect on turnover intention. Other findings reveal that compensation and transactional leadership have a positive effect on job satisfaction. Job satisfaction, in turn, has a negative and significant effect on turnover intention. Furthermore, job satisfaction is proven to mediate the relationship between transactional leadership and turnover intention, but it does not mediate the effect of compensation on turnover intention.